Predicting Emotional and Social Competence during Early Childhood from Toddler Risk and Maternal Behavior - Blandon, Alysia Y. (2010)
The longitudinal associations between maternal parenting behavior and toddler risk with children’s emotional and social competence were examined during the transition to kindergarten, in a sample of 253 children. Toddler risk was characterized by early externalizing behavior and poor emotion regulation skills. Given that we were interested in the multiple pathways that may result in emotional and social competence, we examined the interactions among maternal parenting behavior and toddler risk. There were some significant interactions; although the pattern of results was not consistent across all competence outcomes. Maternal parenting behavior was not directly associated with children’s emotional and social competence. In some instances, maternal control has differential implications for children’s emotional and social competence dependent upon the child’s level of early risk and maternal positive parenting. Specifically, maternal control tended to be more detrimental for children’s emotional competence during the transition to kindergarten, when children exhibit higher levels of risk. Overall, it appears that there are multiple developmental pathways, depending on child and maternal characteristics that lead to early emotional and social competence.